Are generalists species replacing specialists? Implications of hosts species distribution on tick-borne diseases along an altitudinal gradient in the Italian Alps. - Ferrari, G.; Cagnacci, F.; Devineau, O.; Girardi, M.; Rosso, F.; Rizzoli, A.; Arnoldi, D.; Inama, E.; Tagliapietra, V. (country:NL, 2022)
Introduction In a global change context, the association between generalists and specialists could be a determinant of ecosystem stability. This holds particularly true in mountain ecosystems, where the environmental tolerance of generalists to global warming may lead to upward distributional shifts and thus declining of specialists. As a consequence of this altitudinal expansion, even the parasites that these species carry can shift, eventually promoting the emergence of infectious diseases in newly colonized areas. We examined these relationships in small mammals along an altitudinal gradient of Alpine habitats, analysing the differences in small mammals’ assemblage and pathogens’ occurrence. Methods We capture-mark-recaptured wild small mammals from 500 to 2500 m a.s.l. at 500-meters intervals in the Italian Alps, in 2019 and 2020. We counted ticks on rodents and collected ear biopsy samples. Molecular PCR-based methods coupled with sequencing and serological assays were performed for vector-borne pathogens screening. We analysed small mammal species assemblages and probability of infection along the altitudinal gradient with Redundancy Detrended Analysis (RDA) and Generalized Linear Mixed Models (GLMMs). Results In total we captured 333 animals belonging to 11 species (Apodemus flavicollis, A. sylvaticus, Chionomys nivalis, Microtus arvalis, M. subterraneus, M. agrestis, Myodes glareolus, Sorex araneus, S. alpinus, S. minutus, Crocidura leucodon) and counted 3782 ticks (3718 larvae and 64 nymphs) belonging to the genus Ixodes. A. flavicollis and My. glareolus occupied in sympatry the montane belts, from 500 to 1500 m a.s.l. My. glareolus was also present in the alpine belts, from 2000 to 2500 m, together with C. nivalis, Microtus spp. and shrews. We also detected an unevenly altitudinal pattern of distributions of vector-borne pathogens, with Borrelia spp. occurring up until 1500 m a.s.l. (prevalence 13.88%), while Anaplasma phagocytophilum (7.09%) and Babesia microti (3.08%) mainly recorded in alpine belts. ...